DIGITAL MEDIA LAW a practical guide for the media and entertainment industries. - Reed, Christopher S. ([S.l.] : ROUTLEDGE, 2022)
Digital Media Law offers a practical guide to the law of media and communication, focusing on digital channels, models, and technologies. It draws together the aspects of media law that are most critical for those engaged in the production and distribution of digital media, from traditional broadcasters and internet-based services to major internet platforms. As an expert scholar and educator in media law, Christopher S. Reed brings considerable experience as an in-house lawyer for a U.S.-based media company with extensive news, sports, and entertainment operations. This blend of practical and scholarly insight delivers a textbook which packs foundational principles and concepts into the context of the digital environment, focusing on how those doctrines are applied in the face of rapidly evolving newsgathering, production, and distribution technologies. Key features include: "In the News" sections that tie the legal principles to real-world events or situations An integrated fictional case study of a media enterprise Insights into digital media policy This accessible textbook is the ideal companion for advanced undergraduate and graduate students as well as practitioners interested in law, journalism, and media studies.
Keywords: Digital media -- Law and legislation -- United States; LAW / Media & the Law; LAW / Corporate; LAW / Business & Financial